2018
DOI: 10.1111/gbb.12450
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of visual motion perception ability in mice with knockout of the dyslexia candidate susceptibility gene Dcdc2

Abstract: Developmental dyslexia is a heritable disability characterized by difficulties in learning to read and write. The neurobiological and genetic mechanisms underlying dyslexia remain poorly understood; however, several dyslexia candidate risk genes have been identified. One of these candidate risk genes-doublecortin domain containing 2 (DCDC2)-has been shown to play a role in neuronal migration and cilia function. At a behavioral level, variants of DCDC2 have been associated with impairments in phonological proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 89 publications
(184 reference statements)
2
6
0
Order By: Relevance
“…Indeed, our previous results showed that the motion deficit can be observed only at high spatial frequency, at short exposure where eye movement cannot play a role, and at low contrast: these are the stimulus characteristics where motion detectors are particularly fragile in detecting direction. Corroborating our observation in humans, murine models of the same genetic alterations show impairments in motion perception (Rendall et al 2017), together with other sensory deficits (Gabel et al 2012;Truong et al 2015;Centanni et al 2016), suggesting that dyslexics carriers of DCDC2 mutation may constitute a specific subtype of dyslexia where the sensory deficits are a distinctive feature. Given the importance of the issue, we present here evidence that the DCDC2 deletion have deficit in white matter that correlates with the motion deficit, strengthening the suggestion that dyslexia phenotypes with DCDC2 alteration may have different behavioral and brain structure and should be subclustered in the large population of poor readers.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Indeed, our previous results showed that the motion deficit can be observed only at high spatial frequency, at short exposure where eye movement cannot play a role, and at low contrast: these are the stimulus characteristics where motion detectors are particularly fragile in detecting direction. Corroborating our observation in humans, murine models of the same genetic alterations show impairments in motion perception (Rendall et al 2017), together with other sensory deficits (Gabel et al 2012;Truong et al 2015;Centanni et al 2016), suggesting that dyslexics carriers of DCDC2 mutation may constitute a specific subtype of dyslexia where the sensory deficits are a distinctive feature. Given the importance of the issue, we present here evidence that the DCDC2 deletion have deficit in white matter that correlates with the motion deficit, strengthening the suggestion that dyslexia phenotypes with DCDC2 alteration may have different behavioral and brain structure and should be subclustered in the large population of poor readers.…”
Section: Introductionsupporting
confidence: 76%
“…Animal models of DCDC2 deletion have suggested that DCDC2 gene is important for neuronal migration in utero (Poelmans et al, 2011). Interestingly, Rendall et al, (2017) have demonstrated that in the DCDC2d+ KO mouse LGN neurons are smaller in size, suggesting alteration at the thalamic level. The KO mice are also impaired in motion discrimination, corroborating the influence of the DCDC2 neuronal migration in shaping early visual pathways (Rendall et al 2017).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reading disability is a heritable neurodevelopmental condition with a typical age of identification between 7 and 10 years old and affects about 10% of all school‐aged children (Kamhi & Catts, 2012). Reading disability is a complex disorder affecting a number of skills and abilities, including problems with decoding (Catts, 2017), delayed and disordered phonological processing (Beitchman & Young, 1997; Clercq et al, 2017; Peter, Lancaster, Vose, Middleton, & Stoel‐Gammon, 2017), reduced language functioning (Tomblin, Zhang, Buckwalter, & Catts, 2000; Torppa, Lyytinen, Erskine, Eklund, & Lyytinen, 2010), potential deficits in working memory performance (Beneventi, Tonnessen, & Ersland, 2009; Cirino et al., 2018), and abnormal auditory and visual processing (Rendall, Perrino, LoTurco, & Fitch, 2019; Sharma, Purdy, & Kelly, 2009; Sperling, Lu, Manis, & Seidenberg, 2005). Additionally, individuals with reading disability process reading, language, auditory, and visual information differently compared to peers in neuroimaging studies (D'Mello & Gabrieli, 2018; Martin, Kronbichler, & Richlan, 2016; Martin, Schurz, Kronbichler, & Richlan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Buckwalter, & Catts, 2000;Torppa, Lyytinen, Erskine, Eklund, & Lyytinen, 2010), potential deficits in working memory performance (Beneventi, Tonnessen, & Ersland, 2009;Cirino et al, 2018), and abnormal auditory and visual processing (Rendall, Perrino, LoTurco, & Fitch, 2019;Sharma, Purdy, & Kelly, 2009;Sperling, Lu, Manis, & Seidenberg, 2005). Additionally, individuals with reading disability process reading, language, auditory, and visual information differently compared to peers in neuroimaging studies (D'Mello & Gabrieli, 2018;Martin, Kronbichler, & Richlan, 2016;Martin, Schurz, Kronbichler, & Richlan, 2015).…”
mentioning
confidence: 99%